GREEN PURCHASE INTENTION ANALYSIS FOR MENSTRUAL CUP PRODUCTS - Laili, Annisa Nur; Widyastuti, Dominica Arni (APPS Publications, 2023)
This research discusses sustainability that impacts the environment. We as humans find it very difficult not to coexist with objects that have plastic materials. Especially for women, who use sanitary napkin products for single use and have a negative impact on the environment and for the women themselves can be attacked by diseases, Such as cancer. Menstrual Cup is a replacement product for disposable sanitary napkins that has better benefits compared to other menstrual products. However, in Indonesia itself, Menstrual Cup is still something foreign and taboo because of the way it is used and the negative stigma given to consumers. The research that has been conducted aims to determine how much influence Green Product Knowledge and Consumer Doubts have on the Green Purchase Intention of Menstrual Cup products. This research used Explanatory Research with a quantitative approach. Data was collected online using a web link from Qualtrics Survey, using a Semantic Differential scales. The questionnaire link was distributed through social media such as: Whatsapp, Instagram and so on. The number of respondents taken was 128 Gen Z female respondents who have experienced menstruation and who have never used a menstrual cup. The data was processed using Multiple Linear Regression. The research method used is quantitative research using multiple linear regression analysis. The findings of this study are that there is a positive influence of the Green Product Knowledge variable and the Consumer Doubt variable which does not have a significant effect on Green Purchase Intention. The results of this study can provide insight to companies and future researchers. It is also hoped that this research can be expanded to include and focus on single or married women, Gen Z, Gen Millennials and others. The limitation of this research is on Gen Z women in Jakarta who have never used menstrual cup products. There is not much research about menstrual cup, especially in Jakarta Indonesia.